2018
DOI: 10.1016/j.jcf.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Do cystic fibrosis centres with the lowest FEV1 still use the least amount of intravenous antibiotics? A registry-based comparison of intravenous antibiotic use among adult CF centres in the UK

Abstract: CF centres with lowest FEV are still distinguished by lower use of intravenous antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…5 Australia also delivered more aggressive treatment for pulmonary exacerbations, 5 which contributes to better lung health. [16][17][18] Despite the very strong correlation between nutritional outcomes and lung health, [19][20][21] were actually similar between Australian and US children. 5 In fact, Australian children had significantly lower FEV 1 after adjusting for the mode of diagnosis.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…5 Australia also delivered more aggressive treatment for pulmonary exacerbations, 5 which contributes to better lung health. [16][17][18] Despite the very strong correlation between nutritional outcomes and lung health, [19][20][21] were actually similar between Australian and US children. 5 In fact, Australian children had significantly lower FEV 1 after adjusting for the mode of diagnosis.…”
Section: Discussionmentioning
confidence: 90%
“…The 2003 US‐Australia comparison found greater height and weight percentiles among Australian children (suggesting better nutritional outcomes), which is not surprising given that Australian children were much more likely to be diagnosed after newborn screening (65.8%) compared with US children (7.2%) . Australia also delivered more aggressive treatment for pulmonary exacerbations, which contributes to better lung health . Despite the very strong correlation between nutritional outcomes and lung health, FEV 1 were actually similar between Australian and US children .…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies using data from the Epidemiologic Study of Cystic Fibrosis (ESCF) during 1995‐1996 and 2003‐2005 found that CF centers with highest FEV1 used more IVABs. The UK CF registry analyzed data from 28 adult CF centers separately for the years 2013 (4269 adults) and 2014 (4644 adults) to examine whether this was still an association . Centers were ranked by FEV1 quartiles as done in the ESCF analyses.…”
Section: Pulmonary Healthmentioning
confidence: 99%
“…The UK CF registry analyzed data from 28 adult CF centers separately for the years 2013 (4269 adults) and 2014 (4644 adults) to examine whether this was still an association. 57 Centers were ranked by FEV1 quartiles as done in the ESCF analyses. The differences in FEV1 were clinically and statistically significant.…”
Section: Pex: Treatmentmentioning
confidence: 99%
“…But even the CF programs with the best outcomes seem to have provided no antibiotic treatment in about half of the apparent PEx . This ESCF analysis is based on data that is about 20 years old, but a recent publication from the UK still reported that adults with CF attending centers in the upper quartiles for ppFEV1 are 30‐50% more likely to receive at least one IV antibiotic course per year compared to those attending centers in the lowest quartile …”
Section: Variation and Inconsistency In Diagnosis And Likelihood Of Tmentioning
confidence: 99%